A longitudinal study of the durability of long-lasting insecticidal nets in Zambia. (December 2016) - Tan, Kathrine; Coleman, Jane; Smith, Barbara; Hamainza, Busiku; Katebe-Sakala, Cecilia; Kean, Casey; Kowal, Ashley; Eng, Jodi; Parris, Tiffany; Mapp, Carla; Smith, Stephen; Wirtz, Robert; et al.
Abstract Background A key goal of malaria control is to achieve universal access to, and use of, long-lasting insecticidal nets (LLINs) among people at risk for malaria. Quantifying the number of LLINs needed to achieve and maintain universal coverage requires knowing when nets need replacement. Longitudinal studies have observed physical deterioration in LLINs well before the assumed net lifespan of 3 years. The objective of this study was to describe attrition, physical integrity and insecticide persistence of LLINs over time to assist with better quantification of nets needing replacement. Methods 999 LLINs distributed in 2011 in two highly endemic provinces in Zambia were randomly selected, and were enrolled at 12 months old. LLINs were followed every 6 months up to 30 months of age. Holes were counted and measured (finger, fist, and head method) and a proportional hole index (pHI) was calculated. Households were surveyed about net care and repair and if applicable, reasons for attrition. Functional survival was defined as nets with a pHI <643 and present for follow-up. At 12 and 24 months of age, 74 LLINs were randomly selected for examination of insecticidal activity and content using bioassay and chemical analysis methods previously described by the World Health Organization (WHO). Results A total of 999 LLINs were enrolled; 505 deltamethrin-treated polyester nets and 494 permethrin-treated polyethylene nets. With 74 used to examine insecticide activity, 925 were available for full follow-up. At 30 months, 325 (33 %) LLINs remained. Net attrition was primarily due to disposal (29 %). Presence of repairs and use over a reed mat were significantly associated with larger pHIs. By 30 months, only 56 % of remaining nets met criteria for functional survival. A shorter functional survival was associated with having been washed. At 24 months, nets had reduced insecticidal activity (57 % met WHO minimal criteria) and content (5 % met WHO target insecticide content). Conclusions The median functional survival time for LLINs observed the study was 2.5–3 years and insecticide activity and content were markedly decreased by 2 years. A better measure of net survival incorporating insecticidal field effectiveness, net physical integrity, and attrition is needed.